Novel Analytical Method For The Determination Of Atenolol In Pharmaceutical Preparations (Journal of the College of Basic Education, 2022)
An accurate, and sensitive novel method was designated chemically for the determination of atenolol in pharmaceutical drugs. The complex formation between copper(II) and atenolol was studied both in aqueous and methanolic media. Complex formation depend on reaction conditions at different metal-to-ligand molar ratios. The mononuclear violet complex cation Cu(Atenolol)4+2 contains two ligands in an anionic bidentate form (through the hydroxyl oxygen and amino nitrogen) and two in a neutral form bound monodentately with an distorted octahedral geometry. The new analatical method based on measuring absorbance in UV-visible at λmax 350nm. Optimum pH and divalent copper ion concentration were estimated. Linearity(40-250), detection limit 07*10-7M. were determined. The complex is identified with UV-visible and IR spectra. The molar ratio also investigated and found 1:4(Cu:Atn).